Blake, Politics, and History - DiSalvo, Jackie; Rosso, G. A.; Hobson, Christopher Z. (Garland Pub., 1998)
Keywords: 18th century; Politics and literature; 19th century; Political poetry; English; Blake; William; 1757-1827; Great Britain; History; History and criticism; Literature and society; History; Literature and history; History; Social problems in literature; Political and social views; Politics and literature; dept.eng; faculty_collection

You Can Write Poetry - Mock, Jeff (Writer's Digest Books, 1998)
Keywords: Authorship; Creative writing; Poetry; dept.eng; faculty_collection

Is This the End of Little Rico? - Ort, Daniel (Orchises, 1998)
Keywords: 20th century; Biography; Storytelling; Ort; Daniel; 1936-; Authors; American; dept.eng; faculty_collection

Floating - Troy, Robin (MTV : Pocket Books, MTV, 1998)
A woman whose husband is in jail has an affair with his brother, but the two discover too many differences and part. The novel, a debut in fiction, is based on the winning manuscript in a contest of some five hundred entries.
Keywords: Fiction; Fiction; Arizona; Fiction; Married women; Fiction; Mothers and sons; Prisoners' spouses; dept.eng; faculty_collection

Meeting minutes as symbolic action - Mceachern, Robert W (Journal of Business and Technical Communication, 1998)
Postmodern assumptions employed by some organizational theorists recognize that “administrators' greater power lies not in their ability to control resources but in their ability to manipulate symbols-the ceremonies, rituals, images, and language of the organization” (Graham and David 9). Thus, even a genre that is often considered neutral and objective, such as meeting minutes, can become a tool Of managerial control. This article presents data from an ethnographic case study that describes how an administrator in a theater organization manipulated language by using the minutes from a board of directors meeting to influence board members to vote to disband the organization.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/160-831-193-675-812 tex.type: [object Object]
Keywords: dept.eng

Ethnoporn, lesbian childhood, and native maternal culture - Reading National Geographic with Elizabeth Bishop - Blackmer, CE (Glq-a Journal of Lesbian and Gay Studies, 1998)
1 citations (Crossref) [2023-10-31] tex.orcid-numbers: Blackmer, Corinne/0000-0002-9058-5369 tex.unique-id: ISI:000071125400002
Keywords: dept.eng

A medieval scientific encyclopedia "renewed by goodly printing"; Wynkyn de Worde's English De proprietatibus rerum. - Holbrook, Sue Ellen (Early Science and Medicine, 1998)
Wynkyn de Worde published c. 1495 the first printed edition of John Trevisa's English translation of an influential work of science composed by Bartholomew the Englishman in Latin in the thirteenth century, De Proprietatibus Rerum (DPR). The design of de Worde's book, the use of Latin in the rubrics, and the visual vocabulary of the illustrations bring readers of English into the circle of learning. First, the plan of organization of Bartholomew's encyclopedic work is analyzed and both that structure and the expository style of the work are related to memorial reading and use as a textbook. Next, the widespread use of DPR in Latin and vernacular languages is reviewed, the suggestion that certain of its books seem to have been used more than others is made, and the reliance of English readers, such as Roger Thorney, who commissoned de Worde's edition, on de Worde for learned books printed in their provincial tongue is pointed out. Finally, through comparison with certain manuscript and other printed editions, the methods de Worde used to make the book readable are explained, the layout is shown to support the idea of system, and the function of the pictures as visual texts carrying scientific ideas is demonstrated. © Koninklijke Brill NV, Leiden, 1998.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/083-374-886-228-212 tex.type: [object Object]
Keywords: Encyclopedias; Great Britain; History; 15th Century; History; Medieval; Printing; Science; Translations; United Kingdom; article; book; dept.eng; history; printing; publication; science